The role of the media in fostering democracy in Zimbabwe - Mungoshi, Ray (Centre for Law and Society, 2026)
Since 2000, Zimbabwe's ruling party, the Zimbabwe African National Union Patriotic Front (Zanu PF) has methodically stifled democracy in the country by compromising the independence of the judiciary, the professionalism of the police; and intimidating the media. Over the last decade, the party has rid both the state media and the judiciary of impartial journalists and judges, and filled these institutions with its followers. The party purchases its supporters loyalty with presents of farms, expensive vehicles and scarce accoutrements of the consumer society. These material inducements have assisted Zanu-PF to drill an inequitable partisanship into the obsequious state media and instruct journalists to blackout opposition politicians to stymie resistance to its hegemony.1 State media practitioners and the judicial officers' bias have contributed heavily to Zimbabwe's current catastrophic human rights situation. In a practical sense, these openly partisan institutions disingenuously enforce Zanu PF's disastrous policies. While the media market government propaganda, and discredit its opponents, the judiciary is provided with instructions to jail opposition supporters, and issue judgments aimed at perpetuating Zanu PF supremacy.